The emerging marijuana retail environment: Key lessons learned from tobacco and alcohol retail research. (June 2018) - Berg, Carla J.; Henriksen, Lisa; Cavazos-Rehg, Patricia A.; Haardoerfer, Regine; Freisthler, Bridget
Abstract: The emerging retail market for recreational marijuana use warrants research and surveillance as such markets are established in more US states. This research can be informed by the existing literature regarding tobacco and alcohol, which highlights the impact of spatial access to tobacco and alcohol retailers and exposure to tobacco and alcohol marketing on smoking and drinking among youth and young adults. Prior research indicates that tobacco and alcohol retailers, as well as medical marijuana dispensaries, are disproportionately located in neighborhoods characterized by socioeconomic disadvantage and by higher proportions of racial/ethnic minorities and young adults. Moreover, retail marketing or point-of-sale practices may differentially target subpopulations and differ by neighborhood demography and local policy. This literature and the methods employed for studying the tobacco and alcohol market could inform research on the retail environment for marijuana, as current gaps exist. In particular, much of the existing literature involves cross-sectional research designs; longitudinal studies are needed. Moreover, standardized measures are needed for systematic monitoring of industry marketing practices and to conduct research examining neighborhood differences in exposure to retail marketing for marijuana and its contribution to use modality and frequency, alone and in combination with nicotine and alcohol. The use of standardized measures for tobacco and alcohol marketing have been critical to develop an evidence base from cross-sectional and longitudinal studies that document the impact of retail marketing on substance use by adolescents and adults. Similar research is needed to establish an evidence base to inform federal, state, and local regulations of marijuana. Highlights: The relatively new marijuana retail market warrants research and surveillance. The literature regarding tobacco and alcohol retail can inform this work. Tobacco and alcohol retailer location and marketing may impact substance use. These retailers may differentially target vulnerable populations. Gaps in the literature need to be addressed in order to inform research and policy.